Anti-SARS-CoV-2 immunoglobulin profile in patients with celiac disease living in a high incidence area. Issue 1 (January 2022) - Elli, Luca; Facciotti, Federica; Lombardo, Vincenza; Scricciolo, Alice; Sanders, David S.; Vaira, Valentina; Barisani, Donatella; Vecchi, Maurizio; Costantino, Andrea; Scaramella, Lucia; dell'Osso, Bernardo; Doneda, Luisa; et al.
Abstract: Background and aim: How symptoms and antibodies related to SARS-CoV-2 infection develop in patients with celiac disease (CD) is unclear. We aimed to investigate the impact of SARS-CoV-2 infection in CD patients. Methods: CD patients were interviewed about the development of COVID-19 symptoms, compliance with anti-virus measures and adherence to a gluten-free diet (GFD). The presence of anti-SARS-CoV-2 IgG and IgA (anti-RBD and N proteins) was compared to that in non-CD subjects. Expression of the duodenal ACE2 receptor was investigated. When available, data on duodenal histology, anti-tissue transglutaminase IgA (tTGA), comorbidities and GFD adherence were analyzed. Results: Of 362 CD patients, 42 (12%) reported COVID-19 symptoms and 21% of these symptomatic patients presented anti-SARS-CoV-2 Ig. Overall, 18% of CD patients showed anti-SARS-CoV-2 Ig versus 25% of controls ( p = 0.18). CD patients had significantly lower levels of anti-N IgA. tTGA, duodenal atrophy, GFD adherence or other comorbidities did not influence symptoms and/or antibodies. The ACE2 receptor was detected in the non-atrophic duodenal mucosa of patients; atrophy was associated with lower expression of the ACE2 receptor. Conclusion: CD patients have an anti-SARS-CoV-2 Ig profile similar to non-celiac controls, except for anti-N IgA. No risk factors were identified among CD parameters and GFD adherence.